Effect of paddling cadence on time to exhaustion and VO2 kinetics at the intensity associated with VO2max in elite white-water kayakers - Leveque, J. M.; Brisswalter, J.; Bernard, O.; Goubault, C. (Canadian Journal of Applied Physiology, 2002)
The influence of paddling cadence on the time to exhaustion (t.lim) and VO2 kinetics at the intensity associated with VO2max (IVO2max) was examined in seven highly-trained white water kayakers. All subjects were engaged in national or international competitions. Subjects took part in three constant-load tests at IVO2max, each test performed at a different paddling cadence (50, 60 or 70 cycles min(-1). The VO2 kinetics recorded during these constant-load tests at IVO2max were fitted with a mono-exponential equation. A significant increase in t.lim (P <.05) was observed as the paddling cadence increased from 50 to 70 cycles min(-1). No effect was found either on values of VO2peak, post-exercise blood lactate concentration, or on the time at which VO2peak was attained (TAVO2peak). Our results suggest that experienced kayakers may choose a high paddling cadence during physiological assessments at IVO2max. Further experiments are needed in order to identify the physiological significance of t.lim at IVO2max.